(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
In recent years, various kinds of cloak devices were designed by transformation optics, but these cloak metamaterials are anisotropic and difficult to manufacture. In this paper, we designed the isotropic cloak metamaterials based on the numerical method of the optimization theory to the inverse medium problem. This method has universality, and it is not limited by the shape and type of the cloak device. This isotropic material is easier to manufacture in practice than anisotropic material. A large number of numerical results show the effectiveness of the method.